Quality Planning and Project Success in Electricity Supply Infrastructure Projects in Kenya; A Case of Transmission Infrastructure Projects - Okombe, Lee Alubala; Gichuhi, Kimani; Njuguna, Jane Nyokabi; Obunga, Fredrick (European Scientific Journal, ESJ, 2023)
Electricity access is a challenge facing many countries in the world more so the developing ones. This challenge is more pronounced in sub-Saharan Africa, where about 597 million people (43%) lack access to electricity. To address the challenge many countries are investing in electricity supply infrastructure projects such as transmission and distribution lines and power plants. Implementation of such projects is however faced with various challenges resulting in failure to achieve the intended objectives. Scholars have proposed solutions to address these challenges but available literature indicates the issue of quality planning in projects has not been exhaustively addressed. The main objective of this study was to assess the influence of quality planning on project success among electricity supply infrastructure projects in Kenya. The study was anchored on the Deming cycle and the Iron Triangle theories. A descriptive study design was employed in this research. The study population was drawn from the Kenya Electricity Transmission Company staff, which implements electricity transmission projects in Kenya. A stratified sampling method coupled with Yamane’s formula was employed to identify the sample size of 80 among the staff. 63 responses from the surveyed staff were obtained and used for the analysis translating to a 78.75% response rate. The findings showed that the study accepted the alternative hypothesis and concluded that there is a significant and positive influence of quality planning on project success. This study concludes that quality planning is a critical factor that enhances project success in electricity infrastructure projects.